Interface application development of an electrometer using LabVIEW programming to study current-voltage characteristics of semiconductor devices - Karim, Khondker Jeaul (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2016.